1976
DOI: 10.1111/j.1365-2621.1976.tb01153.x
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICAL AND SENSORY ANALYSIS OF ROUNDNOSE GRENADIER (Coryphaenoides rupestris) STORED IN ICE

Abstract: Roundnose grenadier (Coryphaenoides rupestris) was stored in ice in order to investigate changes in chemical and sensory characteristics. Analyses indicated that the keeping time of at least 18 days was better than that of most species of whitefish. Total lipid and free fatty acid concentration did not significantly change during iced storage. Inosine monophosphate, inosine, hypoxanthine, iodine number, peroxide value, thiobarbituric acid value, trimethylamine content determined by the Tozawa method, trimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…This variation in results may be due to different storage conditions, but perhaps equally important is the sensory evaluation procedure (in the present study, no taste testing of raw sardines was involved). The TBA data obtained in the present study for the raw fish appeared to be more consistent than those observed with other marine fishes (Botta and Shaw, 1975;1976).…”
Section: Discussionsupporting
confidence: 88%
“…This variation in results may be due to different storage conditions, but perhaps equally important is the sensory evaluation procedure (in the present study, no taste testing of raw sardines was involved). The TBA data obtained in the present study for the raw fish appeared to be more consistent than those observed with other marine fishes (Botta and Shaw, 1975;1976).…”
Section: Discussionsupporting
confidence: 88%
“…However, TMA content does not always correlate with odor and other sensory tests (Botta and Shaw, 1976).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Fish muscle contains only about one-tenth of the collagen found in meat from terrestrial animals (Eskin 1990;Bracho and Haard 1990). Unlike land animals and mollusks (Kuo et d. 1991), collagen does not normally contribute to the cooked texture of bony fish (Hatae et al 1987(Hatae et al , 1990.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike land animals and mollusks (Kuo et d. 1991), collagen does not normally contribute to the cooked texture of bony fish (Hatae et al 1987(Hatae et al , 1990. The cooked texture of iced fish remains the same during storage (Maia et d. 1983) or progressively decreases in firmness (Botta and Shaw 1976;Hatae et al 1988a;Ando m d. 1990; Kim and Haard 1992).…”
Section: Introductionmentioning
confidence: 99%